An empirical test of Houle's typology of professionals - Baiyin Yang; Ronald M. Cervero (Adult Education Research Conference, 1994)
The purpose of this study was to test Houle's typology of professional practitioners and its relationships with their demographic characteristics and their participation in CPE.